Transformasi Pola Pikir Kewirausahaan Mahasiswa Melalui Program Start-Up Halal Berbasis Experiential Learning - Ilma Mahdiya; Abdul Wahab (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital transformation has opened vast opportunities for the younger generation to engage in technology-based entrepreneurship. However, the low level of literacy regarding Sharia-based business among university students remains a major challenge in building a competitive halal startup ecosystem. This community engagement program aims to equip students with both conceptual understanding and practical skills in developing digital businesses aligned with Sharia principles. The program was implemented on May 10, 2025, involving 60 students from UNISKA, UMB, and Poliban. The method employed an educational-dialogical approach based on experiential learning, encompassing interactive seminars, technical workshops, and reflective evaluations. The training materials included the Sharia Business Model Canvas, halal design thinking, Islamic ethical digital marketing, as well as halal legality and certification. The program’s effectiveness was measured through pretest and posttest instruments, which showed a significant improvement in the average score from 58.3 to 82.7. These findings indicate that the program was effective in enhancing students’ understanding and readiness to become halalpreneurs. Furthermore, the experience fostered a transformation in students’ mindsets toward perceiving business as a means of worship and social contribution. The program is recommended to be replicated on a larger scale with cross-sectoral collaboration and support.